Nickel-catalyzed asymmetric transfer hydrogenation of hydrazones and other ketimines - Xu, Haiyan (2015)
We report the use of nickel catalysts for the catalytic transfer hydrogenation of hydrazones and other ketimines with formic acid. Strongly donating bisphosphines must be used to support the catalysts. As in enzymatic catalysis, attractive weak interactions may be important for stereochemical control by the nickel/binapine catalyst.